Fine Motor Skill Development in ADHD-Risk Children: An Intervention Using Loose Parts Collage Activities - Setyowati, Reni; Sukinah, Sukinah (Papanda Publisher, 2025)
Fine motor skill deficits significantly impact academic readiness in preschool children, particularly those at risk for Attention Deficit Hyperactivity Disorder (ADHD). Traditional interventions often fail to accommodate the unique learning characteristics of children with ADHD, necessitating innovative approaches that integrate multisensory engagement with structured skill development. This study investigated the effectiveness of collage activities using loose parts materials in enhancing fine motor skills among preschool children at risk for ADHD. A classroom action research design following the Kemmis and McTaggart model was employed over four weeks at TK Negeri 1 Sangatta Selatan, Indonesia. Eight children aged 4-5 years with ADHD risk factors participated in two intervention cycles, each comprising two collage sessions using diverse loose parts materials. Fine motor skills were assessed across six domains using structured observation checklists with four-point rating scales. Data collection included quantitative assessments, photographic documentation, and teacher interviews. Substantial improvements were observed across all fine motor domains. Pre-intervention assessment revealed that only 25% of participants achieved competent performance levels (BSH/BSB). Following the two-cycle intervention, 100% of children demonstrated competent fine motor skills across all assessed domains. Participants showed enhanced cutting precision, improved pressure control in material adherence, increased scissor manipulation stability, extended attention spans, greater independence in task completion, and improved creativity with precision. Qualitative observations indicated reduced off-task behaviors and increased peer cooperation. The findings demonstrate that collage activities with loose parts materials effectively address fine motor deficits in children at risk for ADHD. The intervention's success supports loose parts theory and provides evidence for inclusive classroom-based approaches that simultaneously enhance motor competencies and attention regulation. The results have significant implications for early childhood educators seeking practical, evidence-based strategies for supporting diverse learners.